2019
DOI: 10.1055/a-0894-4843
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement of Planar and SPECT Tc99m-MIBI Scintigraphy for the Assessment of Hypofunctioning Thyroid Nodules

Abstract: Introduction Thyroid scintigraphy with 99mTc-methoxyisobutylisonitrile (MIBI) is a helpful tool for the risk stratification of thyroid nodules (TN). Whereas a nodule with low or hypointense MIBI uptake has a low risk for malignancy, a hyperintense uptake may indicate a malignant nodule, which requires surgical resection. The appropriate diagnostic or therapeutic regimen of an isointense nodule with an uptake similar to the paranodular tissue is discussed controversially. Aim of this study was to assess the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…MIBI has a high NPV and effectively rules out malignant TNs with notable accuracy, making it essential in the risk stratification of hypofunctioning TNs. However, MIBI imaging has a rather poor positive predictive value [13]. Therefore, refining the diagnostics i. e. by using a semiquantitative method but also using hybrid imaging [13], is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MIBI has a high NPV and effectively rules out malignant TNs with notable accuracy, making it essential in the risk stratification of hypofunctioning TNs. However, MIBI imaging has a rather poor positive predictive value [13]. Therefore, refining the diagnostics i. e. by using a semiquantitative method but also using hybrid imaging [13], is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, MIBI is also used as an unspecific tracer for detection and staging tumors and for detecting parathyroid adenomas with a high sensitivity [12]. MIBI imaging has been employed for decades in the risk stratification of hypofunctioning TNs due to its high negative predictive value (NPV) exceeding 90 %, allowing for the exclusion of malignancy [2,9,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourthly, interobserver variability of MIBI imaging was not tested. However, Schenke et al and Baumgarten et al showed that the interobserver agreement was good for the planar imaging approach and was improved by using the SPECT technique [ 24 , 25 ]. Finally, our study did not address the cost-effectiveness of MIBI imaging in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%